Pengaruh Profitabilitas Terhadap Intial Return Dilihat Dari Aspek Cash Basis Dan Accrual Basis (Studi Pada Perusahaan Yang Melakukan Initial Public Offering (Ipo) Di Bursa Efek Indonesia Periode Januari 2011 – Agustus 2015) - Febriani, Miranti Dewi; Soesetio, Yuli; Wijijayanti, Trisetia (UNIVERSITAS NEGERI SURABAYA, 2017)
AbstractThe study aims to examine the effect of profitability on Initial Return based on cash basis and accrual basis. The population in this study is companies performing IPO in period of January 2011 – Augustus 2015 as many as 111 companies and are adjusted to several criteria in order to get as many as 70 companies for model 1, 72 companies for model 2, and 53 companies for model 3. It uses simple regression analysis technique assisted by Gretl Software. Interstingly, only ROE affect Initial Return and model 1 has highest R2.